2006
DOI: 10.4049/jimmunol.177.7.4262
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: T Cell Requirement for CD28 Costimulation Is Due to Negative Regulation of TCR Signals by PTEN

Abstract: Recent studies suggest that the phosphatase and tensin homolog deleted on chromosome 10 (PTEN) plays a critical role in the maintenance of self-tolerance. Using T cell-specific PTEN knockout mice (PTENΔT), we have identified a novel mechanism by which PTEN regulates T cell tolerance. We found that TCR stimulation alone, without CD28 costimulation, is sufficient to induce hyperactivation of the PI3K pathway, which leads to enhanced IL-2 production by naive PTENΔT T cells. Importantly, as a result of this increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 24 publications
10
70
0
2
Order By: Relevance
“…5D). In the control PBS-injected group, 100% of tPTEN Ϫ/Ϫ mice (n ϭ 16) had died by 15 weeks of age as expected (12,34). Forty percent of dexamethasone-treated tPTEN Ϫ/Ϫ mice died Ϸ3-4 weeks later, consistent with the idea that reduction of DP thymocytes for 3 weeks led to some delay in lymphoma development.…”
Section: Transient Reduction Of Dp Thymocytes Within a 3-week Windowsupporting
confidence: 66%
“…5D). In the control PBS-injected group, 100% of tPTEN Ϫ/Ϫ mice (n ϭ 16) had died by 15 weeks of age as expected (12,34). Forty percent of dexamethasone-treated tPTEN Ϫ/Ϫ mice died Ϸ3-4 weeks later, consistent with the idea that reduction of DP thymocytes for 3 weeks led to some delay in lymphoma development.…”
Section: Transient Reduction Of Dp Thymocytes Within a 3-week Windowsupporting
confidence: 66%
“…This was supported by a previous study, which revealed that PTEN deficiency serves an important function in the oncogenesis of T cell lymphoma (21), and Pten-knockout mice will develop T cell lymphoma uniformly within 10-16 weeks (22)(23)(24)(25). No significant difference in the expression levels of PTEN in the control, tumor and non-tumor groups of the liver, kidney and spleen were identified, indicating that there was no association between PTEN expression level and thymic lymphoma metastasis.…”
Section: Discussionsupporting
confidence: 68%
“…However, it is difficult to judge from this type of analysis whether PTEN-null T cells traffic normally in the periphery because T cell numbers in secondary lymphoid organs are determined by a balance of the following factors: the efficiency of transendothelial migration from the blood into secondary lymphoid tissue; the homeostatic proliferation of peripheral T cells in the lymphopenic environment found in neonates (Min et al, 2002); and the rate at which cells egress secondary lymphoid tissue (Schwab and Cyster, 2007). In this respect, the enhanced survival and proliferative properties described for PTEN-null peripheral T cells (Suzuki et al, 2001;Buckler et al, 2006) could mask any trafficking problems.…”
Section: Discussionmentioning
confidence: 99%